Professional religious education in Russia = Малайзиядә Профессиональ (һөнәри) Дини Белем - Akhmetova, Elmira (2019)
This paper discusses the history of religious education in Malaysia by stressing on the role of Islam in Malaysian history. It also gives a general overview of Islamic universities with a special reference on IIUM.